Optimization Of Cutting Chicken Routes - Ovi Miru Sunandi; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2021)
This study has the title Optimization of Chicken Cut Retrieval Route. The existence of this study aims to reduce the distance of chicken retrieval routes from cages to slaughter mills, as well as reduce the number of deaths and chicken kesetresan when descending from the chicken carrier fleet. The method in the study used saving matrix method and vehicle routing problem. The method of data collection used is to take primary data that is taken data from the location of cut parik and chicken coop taken by the fleet so far and secondary data taken dati preentase route from the slaughter plant to the chicken coop. And obtained the maximum chicken cut and decreased the death rate and chicken kesetresan with the length of saving matrix route 219.58 Km, using 5 trucks, spent fuel Rp. 141.263, and driver's salary of Rp. 26.250.000. While using vehicle routing problem route length 209.38 Km, using 5 trucks, spent fuel Rp. 134.775, and driver's salary of Rp. 26.250.000.